COMMUNITY STRUCTURE OF CHAETODONTIDAE IN THE WEST OF BANDA SEA - Wibowo, Kunto; Adrim, Mohammad; Makatipu, Petrus Christianus (Marine Research in Indonesia, 2013)
Distribution and composition of Indonesian Chaetodontid species may vary among different locations. However, illegal fishing practices such as bombing and poisoning on reef ecosystems have significant contribution to environmental degradation and can change the community structure of fish especially that of Chatodontids that act as indicator species in in the given areas. Therefore, it is important to do periodic surveys to know the current condition and their changing. A study on community structure of Chaetodontidae has been conducted from July toAugust 2011 on coral reef ecosystems of the Banda Sea and its adjacent waters including Banggai, Kendari, and Lamalera Islands. Scuba equipment was used and underwater visual census method was applied for collecting the data at 21 stations. A total of 1399 individual Chaetodontid fishes was observed, belonging to thirty species and seven genera, i.e. Chaetodon (20 species), Heniochus (4 species), Forcipiger (2 species), Chelmon (1 species), Coradion (1 species), Hemitaurichthys (1 species), and Parachaetodon (1 species). Chaetodon kleinii was the most dominant species in the Banggai (74,38%) and Lamalera (71,71%). Kendari was characterized by the presence of C. octofasciatus that contributed 55,20%. There were two dominant groups of Chaetodontidae based on the feeding guild. Facultative coral feeder was the most abundance in Banggai and Lamalera, while the most commonChaetodontidae in Kendari belonged to obligate coral feeder. Chaetodontid diversity in Banggai was the lowest compared to that of in other studied areas. Anthropogenic pressure may become a major factor causing the low diversity and studied species richness in the coral reef ecosystem of Banggai waters.